The Role of Multiplayer Online Educational Games in Enhancing Critical Thinking - Nuraziera Mohd Hatta; Ibrahim Ahmad; Mohd Hafiz Zakaria; Heru Astikasari Setya Murti; Ulka Chandini Pendit (IJORER : International Journal of Recent Educational Research, 2024)
Objective: This research aims to determine the role of multiplayer online educational games in enhancing students' critical thinking skills. Method: This study utilizes a systematic review method guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach. A comprehensive search was conducted using Scopus, PubMed, and Web of Science (WoS) databases, identifying studies that focused on multiplayer online educational games and their impact on critical thinking skills. Out of 910 studies identified, 20 met the inclusion criteria after a rigorous screening. Results: The results indicate a positive association between multiplayer educational games and enhancing critical thinking skills across various educational settings. Key aspects extracted include game design, educational context, participant demographics, and methodologies for assessing critical thinking outcomes. However, variability in game designs and measurement tools highlights a need for standardized assessment approaches in future research. Novelty: This review underscores the evolving potential of multiplayer online educational games as innovative tools for developing critical thinking skills. With the increasing integration of digital technologies in education, this study sheds light on how game-based learning can address 21st-century educational needs by fostering essential cognitive skills.